Accounting in Multiple Objective Linear Programming. - Kornbluth, J. S. H. (The Accounting Review, 1974)
The article reports that in a situation of decentralized decision making, the Multiple Objective Linear Programming (MOLP) approach provides the decision makers with an appropriate multidimensional scheme of transfer prices. Once again these prices exactly balance the accounts associated with basic products and show opportunity losses for nonbasic products. The transfer prices derived from the MOLP allow central management to calculate the actual divisional contributions to each of the measures of corporate performance, adjusted for the opportunity costs associated with transferred goods. It follows that the divisional targets derived from an MOLP solution are logical and "fair." Operationally and assuming a state of certainty for planning purposes the task of the corporate planner would be to review the various alternative efficient solutions and pick out the "best" or "most desirable." In a situation of decentralized decision making it is already known that the transfer pricing mechanism does not necessarily lead to optimal divisional decisions. This drawback applies equally to MOLP in general and the example in particular.